2021
DOI: 10.1097/ccm.0000000000004921
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Over Time of Ventilatory Management and Outcome of Patients With Neurologic Disease*

Abstract: OBJECTIVES: To describe the changes in ventilator management over time in patients with neurologic disease at ICU admission and to estimate factors associated with 28-day hospital mortality. DESIGN: Secondary analysis of three prospective, observational, multicenter studies. SETTING: Cohort studies conducted in 2004, 2010, and 2016. PATIENTS: Adult patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Indeed, a recent expert consensus (Robba et al, 2020) suggested that in brain-injured patients the levels of PEEP should be the same as for the general critically ill population. Similarly, a survey of the European Society of Intensive Care (Stocchetti et al, 2014) and a recent large multicenter study (Tejerina et al, 2021) suggest that moderate-high levels of PEEP are currently part of the clinical practice of neurocritical care physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent expert consensus (Robba et al, 2020) suggested that in brain-injured patients the levels of PEEP should be the same as for the general critically ill population. Similarly, a survey of the European Society of Intensive Care (Stocchetti et al, 2014) and a recent large multicenter study (Tejerina et al, 2021) suggest that moderate-high levels of PEEP are currently part of the clinical practice of neurocritical care physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence have progressively demonstrated that low V T is associate with favorable outcome after cardiac arrest [37], and very low PEEP or zero PEEP (ZEEP) can aggravate the risk of atelectasis and lung damage [40,41]. As consequence of this, over time, physicians are increasingly applying lower tidal volume and higher PEEP even in cardiac arrest patients [5,42], and as well as in brain injured patients at risk of intracranial hypertension [43]. In a secondary analysis from a multicenter study in ICU patients receiving mechanical ventilation [44], Sutherasan et al showed that in 1998 the mean tidal volume used in cardiac arrest patients was 8.9 mL/Kg, and mean PEEP was 3.5 cmH 2 0 [5].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…However, this result should be interpreted with caution because a lot of data on brainstem impairment were not collected. Given the increased use of PSV in brain-injured patients [ 16 , 26 , 27 ], further studies are warranted in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result should be interpreted with caution because a lot of data on brainstem impairment were not collected. Given the increased use of PSV in brain-injured Table 3 Diagnostic performance of flow index to detect low inspiratory effort using the cutoff value derived from the previous study a a The cutoff value of flow index derived from the previous study was 2.6 [14] Between parentheses is the 95% confidence interval (95% CI) patients [16,26,27], further studies are warranted in this population.…”
Section: Discussionmentioning
confidence: 99%